Association of the D allele of the angiotensin I converting enzyme polymorphism with malignant vascular injury. Issue 1 (1st February 2002) - Mayer, N J; Forsyth, A; Kantachuvesiri, S; Mullins, J J; Fleming, S
Abstract : Aims: To determine whether there is an association between the insertion/deletion (I/D) polymorphism of the human angiotensin I converting enzyme (ACE) gene and malignant vascular injury (MVI). Methods: The polymerase chain reaction was used to genotype DNA extracted from archival, paraffin wax embedded renal biopsy material from 48 patients with MVI, made up from cases of malignant hypertension (n = 23), scleroderma (n = 10), and haemolytic uraemic syndrome (n = 15), and from whole blood samples from 191 healthy controls. Results: The D allele was found more frequently in cases of MVI than in healthy controls, (65% v 52%). Both the DD and I/D genotypes occurred significantly more frequently in patients with MVI than did the II genotype (χ 2 = 7.26, p = 0.007; and χ 2 = 4.06, p = 0.04, respectively). Conclusions: Possession of at least one copy of the D allele is associated with an increased risk of developing MVI. Our data support a dominant mode of effect for the D allele. Use of the I/D polymorphism as a genetic marker for MVI may be of value clinically in identifying at risk individuals before the development of target end organ damage. Furthermore, those at risk may benefit from early ACE inhibition.